Meta-Analisis Praktikalitas Penggunaan E-Learning Berbasis Edmodo Oeh Guru Dan Peserta Didik Dalam Pembelajaran - Risa Anggraini; Ardi Ardi (Universitas Nusantara PGRI Kediri, 2022)
The progress of IPTEK, especially in the field of education, have made the use of tools in the form of learning media more widespread and interactive. One of the learning media that can be developed by teachers is Edmodo-based e-learning. E-learning is a web-based learning medium that can be accessed by the internet. Meanwhile, Edmodo is a simple electronic learning media tool that is used to present lesson content, can be accessed using a smartphone, and is useful for students and teachers to interact online outside the classroom anywhere, anytime. This study aims to analyze the practicality of using Edmodo-based e-learning for teachers and students. Practicality is the degree of ease of use of the product that has been developed. Meta-analysis is done by collecting similar articles by searching for articles from several journals via the internet. The sample used in this study included as many as eight articles related to the use of Edmodo-based e-learning. The results of the study found that the average practicality level of using Edmodo-based e-learning by teachers was 89.15 in the very practical category, while the average practicality level by students was 87.02 in the very practical category. Based on the results of the analysis of the use of Edmodo-based e-learning that was developed, it can be categorized as suitable for use in the learning process.